2023
DOI: 10.3389/fphys.2023.1131201
|View full text |Cite
|
Sign up to set email alerts
|

The roles of sirtuins in ferroptosis

Abstract: Ferroptosis represents a novel non-apoptotic form of regulated cell death that is driven by iron-dependent lipid peroxidation and plays vital roles in various diseases including cardiovascular diseases, neurodegenerative disorders and cancers. Plenty of iron metabolism-related proteins, regulators of lipid peroxidation, and oxidative stress-related molecules are engaged in ferroptosis and can regulate this complex biological process. Sirtuins have broad functional significance and are targets of many drugs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 218 publications
0
4
0
Order By: Relevance
“…Since Npre supplementation results an increase in blood NAD + level ( Figure S1 B), and the GO terms of cluster 7 suggested upregulation of NAD + pathways in both Npre and BU+Npre (Figure 4 D), and considering that sirtuins, a family of NAD + -dependent deacetylases, play a crucial role in ferroptosis and spermatogenesis 29 , 30 , we investigated whether these latter were involved in the beneficial effects exerted by Npre on spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Npre supplementation results an increase in blood NAD + level ( Figure S1 B), and the GO terms of cluster 7 suggested upregulation of NAD + pathways in both Npre and BU+Npre (Figure 4 D), and considering that sirtuins, a family of NAD + -dependent deacetylases, play a crucial role in ferroptosis and spermatogenesis 29 , 30 , we investigated whether these latter were involved in the beneficial effects exerted by Npre on spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In line with these, here, our study observed that the up-regulation of GPX4 and the down-regulation of ACSL4 caused by Npre were counteracted upon suppression SIRT2 expression. A growing number of researches have highlighted that the essential role of SIRT2 in lipid metabolism and oxidation, oxidative stress, and Fe 2+ transport 29 , 48 , suggesting its potential involvement in regulating various biological processes associated with ferroptosis. In terms of lipid metabolism, some studies have reported that SIRT2 decreased the PGC-1α protein level, which further inhibits fatty acid oxidation 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Another target of SIRT1 is nuclear factor erythroid2-related factor 2 (NRF2), which prevents lipid peroxidation, another key contributor to ferroptosis. SIRT1 can manifest anti-ferroptotic effects through the activation of NRF2, a key regulator in the antioxidant stress response, which also affects iron metabolism as it enhances ferritin formation and induces ferroportin [83]. Together, these discoveries demonstrate that NRF2 can efficiently suppress ferroptosis.…”
Section: Influence Of Sglt2 Inhibitors On Erythropoiesis and Iron Hom...mentioning
confidence: 93%
“…Importantly, SIRT1 over-expression induced by SGLT2 inhibitor treatment can suppress ferroptosis and prevent these deleterious consequences of increased cytosolic iron [81,82]. SIRT1 has recently been shown to control ferroptosis by influencing various target genes, among which is p53, the deacetylation of which suppresses ferroptosis [83]. Indeed, many lines of evidence indicate the crucial role of SIRT1 in the regulation of ferroptosis.…”
Section: Influence Of Sglt2 Inhibitors On Erythropoiesis and Iron Hom...mentioning
confidence: 99%